Healing process of venous ulcers: the role of microcirculation. Issue 1 (7th February 2012) - Ambrózy, Ewald; Waczulíková, Iveta; Willfort, Andrea; Böhler, Kornelia; Cauza, Karla; Ehringer, Herbert; Heinz, Gottfried; Koppensteiner, Renate; Marić, Snezana; Gschwandtner, Michael E
<x xml:space="preserve">Abstract</x> In order to describe adequately the process of healing in the intermediate degrees, we investigated microcirculatory changes in the venous ulcers at well‐defined stages of wound repair. We investigated dynamic changes in microcirculation during the healing process of venous ulcers. Ten venous ulcers were investigated in three consecutive clinical stages of wound healing: non granulation tissue (NGTA), GTA and scar. Subpapillary microcirculation was measured by laser Doppler perfusion (LDP) imaging and expressed using LDP values in arbitrary units. Nutritive perfusion by capillary microscopy and expressed as capillary density (CD) – the number of capillaries per square millimetre. Before the development of GTA the LDP was low (median 1·35; lower–upper quartiles 0·71–1·83) accompanied with zero CD in all but one patient who had a density of 1. With the first appearance of GTA in the same area, the LDP was improved (2·22; 1·12–2·33; P = 0·0024) when compared with NGTA, in combination with a significant increase in CD (1·75; 0–3; P = 0·0054). In scar, the LDP was similar to that in the NGTA (1·03; 0·77–1·83; P = 0·278), combined with the highest CD (5·75; 4·5–8) in comparison with the previous stages of the area (for both pairs, P < 0·0001). Venous ulcers are caused by poor nutritive and subpapillary perfusion. Subpapillary perfusion plays a major role in the formation of GTA. In a scar, the increased nutritive perfusion is sufficient to cover the blood supply and keep skin viable while subpapillary perfusion is low.